2019
DOI: 10.1073/pnas.1812947116
|View full text |Cite|
|
Sign up to set email alerts
|

Increased gene copy number of DEFA1/DEFA3 worsens sepsis by inducing endothelial pyroptosis

Abstract: Sepsis claims an estimated 30 million episodes and 6 million deaths per year, and treatment options are rather limited. Human neutrophil peptides 1–3 (HNP1–3) are the most abundant neutrophil granule proteins but their neutrophil content varies because of unusually extensive gene copy number polymorphism. A genetic association study found that increased copy number of the HNP-encoding gene DEFA1/DEFA3 is a risk factor for organ dysfunction during sepsis development. However, direct experimental evidence demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to report PD-induced NLRP3 inflammasome inactivation as a molecular mechanism of mitophagy in SI-AKI. Increasing studies have reported that inflammasome formation-induced activation of pyroptosis plays an important role in inflammatory diseases, including SI-AKI [39][40][41]. In the future, the effects of PD and sirtuins on pyroptosis should be explored further to identify more treatment targets for SI-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to report PD-induced NLRP3 inflammasome inactivation as a molecular mechanism of mitophagy in SI-AKI. Increasing studies have reported that inflammasome formation-induced activation of pyroptosis plays an important role in inflammatory diseases, including SI-AKI [39][40][41]. In the future, the effects of PD and sirtuins on pyroptosis should be explored further to identify more treatment targets for SI-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that genetic copy number variations (CNVs) might be linked to the activation of NLRP3 inflammasome and endothelial pyroptosis. Chen et al found that the human neutrophil peptide (HNP)encoding gene (DEFA1/DEFA3) CNVs play specific roles in sepsis 59 . Interestingly, they reported that transgenic mice carrying more copies of the DEFA1/DEFA3 suffer from more severe sepsis and mortality than those with low copy numbers of DEFA1/DEFA3 and wild-type mice, which is caused by broader endothelial barrier dysfunction and EC pyroptosis.…”
Section: Nlrp3 Inflammasome Activation In Endothelial Cell Deathmentioning
confidence: 99%
“…Also, in a mouse lung microvascular endothelial cell line model, it was reported that HNP-1 induces EC pyroptosis and endothelial barrier dysfunction by directly targeting the purinergic receptor P2X ligand-gated ion channel 7 (P2X7) and subsequently activating the canonical NLRP3/caspase-1 pathway. Functional blockade of HNP1-3 alleviates endothelial pyroptosis and protects the mice from sepsis 59 . This study provided a novel molecular mechanism for NLRP3 activation to mediate endothelial pyroptosis.…”
Section: Nlrp3 Inflammasome Activation In Endothelial Cell Deathmentioning
confidence: 99%
“…Recently, experimental evidence has highlighted the genetic association between the clinical phenotype of sepsis and DEFA-1/DEFA-3 copy number. Transgenic mice models were engineered to produce a high gene copy number of DEFA-1/DEFA-3, which manipulated the outcome of sepsis progression [92]. The consequential effect was compared to the low gene copy number wild-type mice models, in that the former showed chronic inflammation, endothelial cell damage, vascular leakage, severe organ injury, and mortality.…”
Section: Role Of Host Defense Peptides In Inflammationmentioning
confidence: 99%